Improving the patient booking service to reduce the number of missed appointments at East London NHS Foundation Trust Community Musculoskeletal Physiotherapy Service. Issue 2 (31st October 2017) - Tan, Elizabeth; Shah, Amar; De Souza, Warren; Harrison, Mark; Chettur, Chris; Onathukattil, Maimoona; Smart, Michelle; Mata, Marlon; Chitewe, Auzewell; Binley, Emma
Abstract : The East London National Health Service Foundation Trust (ELFT) Community Musculoskeletal (MSK) Physiotherapy Service had reported a high rate of non-attendance at scheduled appointments. This was leading to delayed access to treatment for patients and a reduced capacity for service users, as well as a waste of clinical resources. The aim of this quality improvement project was therefore to reduce the percentage of missed appointments within this department. This study was undertaken by the ELFT community MSK service, with support from the ELFT Quality Improvement team. To begin with, patient complaints were explored; these indicated that the main reason for missing appointments was due to issues with the patient booking service. Baseline data were initially collected for both new referrals and follow-up patients. The proposed changes were then introduced, which included text message reminders, first via a manual platform and then via an automated system. Ongoing data were recorded to note the effectiveness of these changes.Following the intervention, non-attendance of newly referred patients reduced by 43.35% (23.76%–13.46%) after both cycles. Non-attendance of follow-up patients reduced by 44.14% (23.74%–13.26%) after the second cycle alone. By listening to the opinions of service users, it was possible to improve the patient booking system and the flexibility of appointments. This resulted in a reduction in the percentage of appointments missed. These changes will continue to be monitored within this department to ensure sustainability but there is also now potential for similar interventions to be trialled in other health service departments.